Effect of cations substitution in lead-free double perovskite Cs2AgBiBr6 solar cells - Nathan Daem; Anthony Maho; Pierre Colson; Gilles Spronck; Cédric Malherbe; Thi Hieu Hoang; Mohamed-Nawfal Ghazzal; Guorui He; Felix Lang; Rudi Cloots; Jennifer Dewalque (Next Materials)
Cationic substitution can be exploited as strategy to modulate the structural, electronic, and optical properties of perovskite materials. This work investigates the effect of doping Cs2AgBiBr6 double perovskite compounds as 10 at% Rb, Zn, and Sb-substituted formulations, further incorporated in wet-processed solar cells. Impacts on crystal structure, light harvesting, and charge generation mechanisms are highlighted, especially in terms of photoconversion metrics and efficiency. Regardless of the doping atom, the morphology of the spin-coated photoactive layers presents high homogeneity and coverage rate as well as uniform thickness, matching the characteristics of the undoped benchmark. Advantageously, a significant enhancement of the harvested light is established from UV–VIS spectrometry analyses, with the layers optical band gap notably decreasing from 2.32 to 2.20–2.28 eV following substitution. However, photovoltaic efficiencies calculated from J-V measurements drop from 1.6 % with undoped Cs2AgBiBr6, to 1.1, 0.3, and 0.4 % with Rb, Zn, and Sb- substituted formulations. Structural analyses of XRD and tolerance factor calculations, combined with Raman and XPS, rationalize these drops by a crystal lattice being too destabilized from the atomic substitutions, especially in Sb- and Zn-substituted samples, with the latest being further undermined by the occurrence of cationic vacancies. Joined UPS, PL and EIS studies also highlight differences of charge transfer properties in the different configurations of solar cells, notably owing to the materials energy levels (mis)alignment. All in all, the present contribution allows for an in-depth understanding of how such cationic substitutions affect Cs2AgBiBr6 intrinsic behavior and functionality as photovoltaic material, filling a key knowledge gap.